(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article explores the strategic importance of small enterprises (SEs) within creative and cultural industries, emphasizing their roles in economic growth, innovation, and cultural development in Uzbekistan. It outlines how SEs generate employment, enhance national branding, and support tourism while addressing social and environmental objectives through circular-economy practices. Key challenges limited access to finance, skilled labor shortages, market competition, intellectual-property protection, and the tension between creative freedom and commercial viability are analyzed. The paper reviews Uzbekistan’s “2017–2021 Action Strategy” and international best practices (Japan, South Korea, Germany, Turkey, China, Israel, UK), detailing support mechanisms such as concessional loans, grants, subsidies, guarantees, leasing, and venture capital. It also highlights regulatory frameworks, infrastructure needs (incubators, broadband), and export-promotion initiatives. Finally, the authors propose an integrated policy framework combining risk management, capacity building, public-private partnerships, and sustainable practices to foster a vibrant ecosystem where creative SEs can thrive, thereby promoting economic diversification and cultural resilience.